2020
DOI: 10.1016/j.cropro.2020.105307
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of insecticides, physical barriers and size of planting stock against damage by the pine weevil (Hylobius abietis)

Abstract: Effectiveness of insecticides, physical barriers and size of planting stock against damage by the pine weevil (Hylobius abietis). Crop Protection . p. 105307.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…The experiments reported here confirm the efficacy of acetamiprid as part of the integrated pest management of Hylobius, supporting evidence from elsewhere (Hardy et al 2020;Willoughby et al 2020;Moore et al in prep). Our results indicate that pre-treating trees with 0.037 g a.i.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The experiments reported here confirm the efficacy of acetamiprid as part of the integrated pest management of Hylobius, supporting evidence from elsewhere (Hardy et al 2020;Willoughby et al 2020;Moore et al in prep). Our results indicate that pre-treating trees with 0.037 g a.i.…”
Section: Discussionsupporting
confidence: 89%
“…stem −1 chlorantraniliprole is likely to be required in the spring of the second year after planting. Hardy et al (2020) also reported promising levels of protection over two years, similar to that provided by acetamiprid, for 0.013 g a.i. stem −1 chlorantraniliprole, which is the maximum application rate currently permitted for pre-treatment applications in the UK, assuming a standard post-treatment planting density of 2700 stems ha −1 (Health and Safety Executive 2019).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The use of synthetic insecticides is effective and relatively cheap 24 . However, because of adverse environmental effects, insecticide use will be increasingly restricted 2,19,24,25,26 and replaced by various physical feeding barriers 27 .…”
Section: Introductionmentioning
confidence: 99%